Summary of Report to Board of Governors - Vallejo Times-Herald (Vallejo Times-Herald)
Since the opening of the California Maritime Academy here in 1930, says Capt. Henry E. Richter, USN, (Ret.), Academy superintendent, in a report to the Board of Governors, 1,869 students have been admitted and, counting the 66 prospective graduates in the class of 1961, there will be a total of 1,238 graduates by that time.